Bread and roses, too - Paterson, Katherine (New York : Clarion Books, 2006)
Jake and Rosa, two children, form an unlikely friendship as they try to survive and understand the 1912 Bread and Roses strike of mill workers in Lawrence, Massachusetts.
810
Accelerated Reader AR
Keywords: Strikes and lockouts -- Textile workers -- Fiction; Labor unions -- Fiction; Survival -- Fiction; Textile workers -- Fiction; Immigrants -- Fiction; Emigration and immigration -- Fiction; Lawrence (Mass.) -- History -- 20th century -- Fiction; Historical fiction